2012
DOI: 10.1016/j.kjms.2011.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Myelodysplasia followed by Good's Syndrome: A unique manifestation associated with thymoma

Abstract: Good's syndrome, also known as thymoma with combined immunodeficiency, is rare. The immunodeficiency may precede, arise concurrently with or follow the diagnosis of thymoma. In addition to myasthenia gravis and Good's syndrome, paraneoplastic syndromes associated with thymoma can also be manifested with hematological disorders, such as pure red cell aplasia, aplastic anemia, agranulocytosis, hemolytic anemia, pernicious anemia, and paroxysmal nocturnal hemoglobinuria. Myelodysplastic syndrome is a group of clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
4
0
2
Order By: Relevance
“…Thirty studies were identified after screening the titles, abstracts, and authors,[34567891011121314151617181920212223242526272829303132] four of which were excluded (two did not qualify as diagnoses of GS,[1025] whereas the other two[329] were excluded because they reported the same patients as other studies[515]). An unpublished case report of GS was also included.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty studies were identified after screening the titles, abstracts, and authors,[34567891011121314151617181920212223242526272829303132] four of which were excluded (two did not qualify as diagnoses of GS,[1025] whereas the other two[329] were excluded because they reported the same patients as other studies[515]). An unpublished case report of GS was also included.…”
Section: Resultsmentioning
confidence: 99%
“…The most common disorders affecting bone marrow precursors are pure red cell aplasia (PRCA) and ‘pure B cell aplasia’ (Good’s syndrome: thymoma and hypogammaglobulinaemia) (3–4% of patients). A few patients have also been described with agranulocytosis, myelodysplasia or paroxysmal nocturnal haemoglobinuria . The pathogenesis of these complications is thought to involve either the production of autoantibodies, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Los timomas más frecuentemente asociados al síndrome de Good son los tipos AB (41.7 %), B2 (25 %) y B1 (12.5 %), de acuerdo con la clasificación de la Organización Mundial de la Salud. 5,6 La fisiopatología se desconoce, sin embargo, se ha propuesto que un defecto medular provoca que las células B se detengan en estadio preB, ocasionando disminución en la producción de inmunoglobulinas y alteraciones en las series eritroide y mieloide. Otros hallazgos son la disminución de la interleucina 2 (IL-2), anormalidades de la quimiotaxis y aumento de las células T de memoria activadas.…”
Section: Introductionunclassified
“…Otros hallazgos son la disminución de la interleucina 2 (IL-2), anormalidades de la quimiotaxis y aumento de las células T de memoria activadas. 5,6,7 Las manifestaciones clínicas incluyen síntomas secundarios a la compresión ocasionada por el timoma, como tos, disfagia, disfonía o síndrome de vena cava superior, así como infecciones sinopulmonares recurrentes. 7,8,9 Las infecciones son causadas en su mayoría por Haemophilus influenzae y Pseudomonas.…”
Section: Introductionunclassified